2020
DOI: 10.1016/j.lssr.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer progression using fast switching multiple ion beam radiation and countermeasure prevention

Abstract: Most of the research in understanding space radiation-induced cancer progression and risk assessment has been performed using mono-energetic single-ion beams. However, the space radiation environment consists of a wide variety of ion species with a various range of energies. Using the fast beam switching technology developed at the NASA Space Radiation Laboratory (NSRL) at Brookhaven National Laboratory (BNL), ion species can be switched rapidly allowing investigators to use multiple ions with different energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…However, mixed beam studies are nevertheless far more complicated in that, in addition to dose/fluence, the temporal sequence, dose rate and composition of the mixed beams must be taken into consideration. In a recent study, lung cancer tumorigenesis in K-ras LA-1 mice was reported to be dependent on the sequence of H + He + Si vs. Si + He + H [ 38 ]. H + He + Si showed increased incidences of premalignant lesions and systemic oxidative stress in mice 100 days post irradiation when compared to Si + He + H or H alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, mixed beam studies are nevertheless far more complicated in that, in addition to dose/fluence, the temporal sequence, dose rate and composition of the mixed beams must be taken into consideration. In a recent study, lung cancer tumorigenesis in K-ras LA-1 mice was reported to be dependent on the sequence of H + He + Si vs. Si + He + H [ 38 ]. H + He + Si showed increased incidences of premalignant lesions and systemic oxidative stress in mice 100 days post irradiation when compared to Si + He + H or H alone.…”
Section: Discussionmentioning
confidence: 99%
“…CDDO is of particular CNS interest due to proven therapeutic intervention for mouse models of Huntington’s disease, malaria, and ischemic injury (Stack et al, 2010; Crowley et al, 2017; Xu et al, 2017; Lei et al, 2020). In addition, dietary CDDO-EA (400mg/Kg) has proven as an effective countermeasure against GCR-induced lung tumors in tumorigenic mice exposed to 30cGy of a 3-beam mixed field (Luitel et al, 2020). The exact mechanism of charged-particle radiation toxicity on neurons remains unclear, though oxidative stress, being the primary source of radiation interaction with tissues remains a primary therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…CDDO is of particular interest for CNS research due to effective pre-clinical therapeutic intervention for mouse models of Huntington's disease, malaria, and ischemic injury [16][17][18][19]. In addition, dietary CDDO-EA (400mg/Kg) is an effective countermeasure against GCR-induced lung tumors in tumorigenic male mice exposed to 30cGy of a 3-beam mixed field [15]. CDDO-EA was therefore a promising intervention as it offers a multifaceted protective approach by targeting the Nrf-2 pathways, which have protective downstream effects on oxidative stress management, microglial activation, and blood-brain barrier integrity, all of which are adversely affected in the CNS of mice following radiation [77,78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it is assumed that the biological response from a mixed-field irradiation (in particle type and energy), as would be found in space, can be determined by simple additivity or by directly adding responses from individual ions and energies. However, results for Harderian gland tumorigenesis [Siranart et al 2016] and lung cancer tumorigenesis [Luitel et al 2020] in murine models suggest that synergies between particles may exist and that more complex additivity models need to be considered. Emerging models for non-targeted effects (NTE), which have a significant influence on low-dose extrapolations expressed through RBEs, are being developed and have been shown to significantly impact radiation quality factors Cacao 2017, Matsuya et al 2018].…”
Section: VI Addressing Model-form Uncertaintymentioning
confidence: 99%